Anticipating bladder outlet obstruction in enlarged prostate: non-invasive clinical parameters as predictive tools - Muhammad Fayyaz,; Mahar, Naveed Ahmed; Qureshi, Harris Hassan; Kalwar, Sara; Usman Abdul Ahad,; Hashmi, Altaf (Journal of the Pakistan Medical Association, 2025)
Objective: To determine the positive predictive value of clinical evaluation with maximum flow rate, prostatic volume and international prostate symptom score in predicting bladder outlet obstruction due to prostatic enlargement. Method: The cross-sectional, prospective study was conducted at the Urology Department of the Sindh Institute of Urology and Transplantation, Karachi, from September 2021 to May 2023, and comprised male patients with refractory lower urinary tract symptoms in whom surgical intervention had been planned. All patients with prostate volume >40ml, maximum flow rate <8ml/sec and international prostate symptom score >7 were labelled as bladder outlet obstruction cases, and were subjected to urodynamic analysis. They were subsequently labelled as true positive or false positive cases. Data was analysed using SPSS 25. Results: There were 177 male patients with mean age 67.79±8.931 years (range: 40-80 years). Mean duration of symptoms was 5.77±2.822 years. Mean international prostate symptom score was 21.69±2.775, mean maximum flow rate was 4.753±2.0342 and mean prostate volume was 61.243±10.57. Overall, 163(92.1%) patients were true positive, and 14(7.9%) were false positive. The positive predictive value of clinical evaluation to find out bladder outflow obstruction secondary to enlarged prostate was 0.92. Conclusion: Maximum flow rate combined with total prostate volume and international prostate symptom score could be used for the prediction of bladder outflow obstruction. Key Words: Prostate volume, Urinary flow rate, Bladder outlet obstruction, Benign prostatic hyperplasia.